Sawdust pyrolysis from the furniture industry in an auger pyrolysis reactor system for biochar and bio-oil production. (15th December 2020) - Ahmed, Ashfaq; Abu Bakar, Muhammad S.; Sukri, Rahayu S.; Hussain, Murid; Farooq, Abid; Moogi, Surendar; Park, Young-Kwon
Highlights: Potential of acacia sawdust is studied in auger pyrolysis system in range 400 ~ 600 °C. A detailed characterization of the sawdust prior to pyrolysis investigation is studied. Bio-oils showed a higher conc. of oxygenates with the variance of pyrolysis conditions. Increase in temperature decreased the % peak areas for organic acids and ketones. Biochar characterization showed an energy potential comparable to low ranked coals. Abstract: This study investigated the potential of sawdust from the processing of Acacia wood for the furniture making industry to produce bio-oil and biochar in an auger pyrolysis reactor system. The necessary characterization to assess the suitability of feedstock and strategies the pyrolysis parameters was also carried out. The volatile matter, ash content, carbon content and the higher heating value of the sawdust feedstock were reported as 68.46 wt%, 1.13 wt%, 47.40 wt% and 19.33 MJ/kg, respectively, with very low nitrogen and sulfur content. The thermogravimetric (TGA and DTG) analysis of sawdust showed that the weight loss from biomass occurred in three main stages as a result of the removal of moisture and extractives, decomposition of hemicellulose, cellulose, and the lignin components. Based on the decomposition temperature window and peak conversion temperature the pyrolysis experiments were carried out in the range of 400–600 ℃ by maintaining the nitrogen flow rate, biomass feeding rate, rotation speed of the conveyer the residence time of materials and biomass particle size as 300 cm 3 /min, 180 g/h, 4.5 RPM, 5 min, and 0.5–1.0 mm, respectively. The yields of the non-condensable gases, biochar and bio-oil were reported in the ranges 16.70–38.47 wt%, 29.72–51.85 wt% and 29.40–45.10 wt%, respectively. The pyrolysis products were pragmatically analyzed to evaluate the influence on yield and their properties. The higher heating values of bio-oil produced were reported in the range 28.781–29.871 MJ/kg while the pH of bio-oil indicated the strongly acidic nature with values in the range of 2.9–3.4. Chemical compounds in bio-oils were categorized as phenols, nitrogen containing compounds, guaiacols, organic acids, ketones, anhydrous sugars, esters, and aldehydes. Biochar characterization showed an energy potential comparable to those of the low ranked coals with the higher heating values reported in the range of 25.01–25.99 MJ/kg. The surface morphological characteristics and Brunauer–Emmett–Teller (BET) analysis of the biochars indicated potential for other valued applications in the adsorption, environmental, catalyst, and agricultural context.